Local Wisdom in the Era of Industrial Revolution 4.0 in the Context of Art Education - Suherman Suherman; Irman Syarif; Elihami Elihami; Mohd. Melbourne (Universitas Muhammadiyah Enrekang, 2022)
Art Education is an educational program that uses art as a medium or a tool in the process of education and learning. Art in the context of education is used as object or focus study to achieve educational objectives that humanize human beings. This article analyzes conceptually about local wisdom discourse in the era of the Industrial Revolution 4.0 in the context of art education. The results indicated that local wisdom-based art education has an important and strategic role in cultural conservation and development projects, as well as a crucial agent in shaping human characters as that have an reciprocatively, creative, and productive attitude. Through an appreciation and creative creation activities in the implementation of art education, local wisdom in the era of the industrial revolution 4.0 can be saved and developed.